2008
DOI: 10.1111/j.1574-0862.2008.00302.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of NCPB marketing policies on maize market prices in Kenya

Abstract: The Government of Kenya pursues maize marketing policy objectives through the National Cereals and Produce Board (NCPB), which procures and sells maize at administratively determined prices, and stores maize as a contingency against future shortages. A private sector marketing channel competes with the NCPB. This article estimates the effects of NCPB activities on the historical path of private sector prices in Kenyan maize markets between 1989 and 2004. The analysis is carried out using a reduced form vector … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 12 publications
3
64
0
Order By: Relevance
“…In both countries, official producer prices were abolished, private inter-district maize trade legalized and deregulated, maize milling liberalized, and subsidies on maize grain to millers and on refined sifted maize meal to consumers eliminated (Jayne et al, 1996;Jayne and Jones, 1997). Restrictions on external trade were somewhat relaxed in the mid-1990s but, to date, the Kenyan and Zambian governments have continued to use variable maize import tariffs and export bans, even in the ''liberalized'' market environment (Jayne et al, 2007(Jayne et al, , 2008Govereh et al, 2010).…”
Section: Figmentioning
confidence: 96%
“…In both countries, official producer prices were abolished, private inter-district maize trade legalized and deregulated, maize milling liberalized, and subsidies on maize grain to millers and on refined sifted maize meal to consumers eliminated (Jayne et al, 1996;Jayne and Jones, 1997). Restrictions on external trade were somewhat relaxed in the mid-1990s but, to date, the Kenyan and Zambian governments have continued to use variable maize import tariffs and export bans, even in the ''liberalized'' market environment (Jayne et al, 2007(Jayne et al, , 2008Govereh et al, 2010).…”
Section: Figmentioning
confidence: 96%
“…Karanja, Jayne and Strasberg (1998) look at the productivity impacts and Jayne, Myers and Nyoro (2005) at the e¤ect on maize prices over 1990-2004. Hassan, Mekuria and Mwangi (2001 show the …ve fold increase in private seed companies between 1992 and 1996, also documented by Kamau (2002) who points out important legislative and regulatory constraints during this time.…”
Section: Modeling Adoption Decisionsmentioning
confidence: 99%
“…Hence, Nyoro et al (1999) found that 70% of all marketed maize in Kenya came from four districts of the Rift Valley, populated largely by Kalenjin, while the majority of producers in the rest of the country were deficit or net deficit producers. Jayne et al (2008) examine the impact of NCPB buying prices on the maize prices prevailing in Kitale (Rift Valley) and Nairobi wholesale markets over the period [1989][1990][1991][1992][1993][1994][1995][1996][1997][1998][1999][2000][2001][2002][2003][2004]. They find that, in the 1989-94 period, when maize marketing was only partially liberalised, 4 NCPB buying prices served to reduce prices in the two wholesale markets by around 20%.…”
Section: Political Power and State Organisations In Kenyamentioning
confidence: 99%
“…(However, it seems that Ruto did choose the Ministry during the 2007-8 negotiations over the formation of the government of national unity.) Nevertheless, given that President Moi -fellow Kalenjin and architect of the rise of the NCPB -is no longer in power and that many others lose out from the NCPB's maize pricing policy (Jayne et al, 2008;Mghenyi et al, 2011), 10 it is plausible that protection of the rent to surplus maize producers (discussed earlier) has been part of the calculation. Minister Ruto was alleged to have used his position not just to protect maize producer prices, but also to distribute other rents to allies through the sale of fertiliser and maize from government stocks at subsidised prices.…”
Section: Agricultural-sector Ministriesmentioning
confidence: 99%